2021
DOI: 10.3390/polym13050715
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Response and Analysis of Cracking Process in Hybrid TRM Composites with Flax Textile and Curauá Fibres

Abstract: In recent years, the use of plant fibres in Textile-Reinforced Mortar (TRM) composites emerged as a valuable solution to increase their sustainability. Several studies carried out to mechanically characterize the so-called Natural TRMs, although showing promising results, also emphasised some drawbacks due to a severe deformability of the system and to durability issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The lengths associated with longer fibers increased contact with the cement paste while uniform distribution and multidirectional reinforcement of textiles (in both weave directions) could lead to the formation of multiple micro-cracks and improvements in mechanical properties such as tensile and flexing strengths and impact testing [ 18 , 19 , 20 , 21 ]. Some examples were studies considering sustainable textile or unconventional reinforcements such as sisal fibers [ 21 , 22 ], flax-based cellulose textiles [ 23 , 24 ], jute fibers [ 25 , 26 ], nonwoven flax cloth [ 19 , 27 ], and nonwoven cloth from polyester and cotton waste from the garment and textile industries [ 28 ]. The use of textile waste could be further aided with techniques that impregnate it with resin to improve textile-matrix bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The lengths associated with longer fibers increased contact with the cement paste while uniform distribution and multidirectional reinforcement of textiles (in both weave directions) could lead to the formation of multiple micro-cracks and improvements in mechanical properties such as tensile and flexing strengths and impact testing [ 18 , 19 , 20 , 21 ]. Some examples were studies considering sustainable textile or unconventional reinforcements such as sisal fibers [ 21 , 22 ], flax-based cellulose textiles [ 23 , 24 ], jute fibers [ 25 , 26 ], nonwoven flax cloth [ 19 , 27 ], and nonwoven cloth from polyester and cotton waste from the garment and textile industries [ 28 ]. The use of textile waste could be further aided with techniques that impregnate it with resin to improve textile-matrix bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Among those solutions, the use of textile-reinforced mortar (TRM) systems have emerged as a technically viable and economically convenient opinion for seismic strengthening [ 2 ]. TRM systems consist of two “phases”: An inorganic matrix, which is generally represented by a cement- or lime-based mortar, the use of hydraulic lime being more and more common [ 3 , 4 , 5 , 6 ]; An internal reinforcement consisting of a low-density textile made of various types of fibres, such as glass, basalt, carbon, high-strength steel, PBO (p-Phenylene Benzobis Oxazole), and aramid [ 1 , 7 ]. …”
Section: Introductionmentioning
confidence: 99%
“…An inorganic matrix, which is generally represented by a cement- or lime-based mortar, the use of hydraulic lime being more and more common [ 3 , 4 , 5 , 6 ];…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of this research has portrayed natural fibres as prospectively being able to enhance the mechanical and strength properties of mortar. Studies have suggested that these fibres can help delay or stop the propagation of micro-cracks in cementitious composite materials, improve the post cracking behavior of mortar, expand the protection from dynamic loads, improve ductility and toughness, and lower the perviousness of mortar, thus reducing the loss of water [19][20][21]. The reuse of natural fibres in the construction industry would safeguard natural assets that cannot be replenished, diminish the ecological contamination caused by solid wastes, and preserve energy that would otherwise have been utilized during incineration processes [22].…”
Section: Introductionmentioning
confidence: 99%